Incisionless transcranial MR-guided focused ultrasound in essential tremor: cerebellothalamic tractotomy. Issue 1 (December 2016) - Gallay, Marc; Moser, David; Rossi, Franziska; Pourtehrani, Payam; Magara, Anouk; Kowalski, Milek; Arnold, Alexander; Jeanmonod, Daniel
Abstract Background Already in the late 1960s and early 1970s, targeting of the "posterior subthalamic area (PSA)" was explored by different functional neurosurgical groups applying the radiofrequency (RF) technique to treat patients suffering from essential tremor (ET). Recent advances in magnetic resonance (MR)-guided focused ultrasound (MRgFUS) technology offer the possibility to perform thermocoagulation of the cerebellothalamic fiber tract in the PSA without brain penetration, allowing a strong reduction of the procedure-related risks and increased accuracy. We describe here the first results of the MRgFUS cerebellothalamic tractotomy (CTT). Methods Twenty-one consecutive patients suffering from chronic (mean disease duration 29.9 years), therapy-resistant ET were treated with MRgFUS CTT. Three patients received bilateral treatment with a 1-year interval. Primary relief assessment indicators were the Essential Tremor Rating Scale (Fahn, Tolosa, and Marin) (ETRS) taken at follow-up (3 months to 2 years) with accent on the hand function subscores (HF16 for treated hand and HF32 for both hands) and handwriting. The evolution of seven patients with HF32 above 28 points over 32 (group 1) differentiated itself from the others' (group 2) and was analyzed separately. Global tremor relief estimations were provided by the patients. Lesion reconstruction and measurement of targeting accuracy were done on 2-day post-treatment MR pictures for each CTT lesion. Results The mean ETRS score for all patients was 57.6 ± 13.2 at baseline and 25.8 ± 17.6 at 1 year (n  = 10). The HF16 score reduction was 92 % in group 2 at 3 months and stayed stable at 1 year (90 %). Group 1 showed only an improvement of 41 % at 3 months and 40 % at 1 year. Nevertheless, two patients of group 1 treated bilaterally had an HF16 score reduction of 75 and 88 % for the dominant hand at 1 year after the second side. The mean patient estimation of global tremor relief after CTT was 92 % at 2 days and 77 % at 1-year follow-up. Conclusions CTT with MRgFUS was shown to be an effective and safe approach for patients with therapy-refractory essential tremor, combining neurological function sparing with precise targeting and the possibility to treat patients bilaterally.